2016
DOI: 10.1080/13543776.2017.1254194
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid deprivation using enzymes as a targeted therapy for cancer and viral infections

Abstract: Amino acid depletion in the blood serum is currently being exploited and explored for therapies in tumors or viral infections that are auxotrophic for a certain amino acid or have a metabolic defect and cannot produce it. The success of these treatments is because normal cells remain unaltered since they are less demanding and/or can synthesize these compounds in sufficient amounts for their needs by other mechanisms. Areas covered: This review is focused on amino acid depriving enzymes and their formulations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 98 publications
2
45
0
4
Order By: Relevance
“…IAV induces aerobic glycolysis in virus-producing cells and increases glutaminolysis and FA synthesis, presumably to provide carbon sources and energy to fuel virion replication while maintaining infected cell survival (Figure 1 bottom). 9,59 In the 1950s, virologists determined excess glucose and glycolysis were required for maximal IAV replication and virulence, irrespective of the host reservoir. 3,6,7 In the same decade, researchers discovered phagocytosis by polymorphonuclear leukocytes was glucose-dependent, and they attributed inhibition of phagocytosis to blocked energy metabolism.…”
Section: In Vitro Studies Of Iav Metabolismmentioning
confidence: 99%
“…IAV induces aerobic glycolysis in virus-producing cells and increases glutaminolysis and FA synthesis, presumably to provide carbon sources and energy to fuel virion replication while maintaining infected cell survival (Figure 1 bottom). 9,59 In the 1950s, virologists determined excess glucose and glycolysis were required for maximal IAV replication and virulence, irrespective of the host reservoir. 3,6,7 In the same decade, researchers discovered phagocytosis by polymorphonuclear leukocytes was glucose-dependent, and they attributed inhibition of phagocytosis to blocked energy metabolism.…”
Section: In Vitro Studies Of Iav Metabolismmentioning
confidence: 99%
“…As such, the use of ASP can produce an anticancer effect by breaking down circulating asparagine and leaving cancer cells unable to synthesize necessary nucleic acids and proteins. 11,12 Several retrospective studies showed that gemcitabine, oxaliplatin, and l-ASP (GELOX) and gemcitabine, oxaliplatin, and pegasparaginase (P-GEMOX) regimens were effective and well tolerated in patients with ENKTCL in several previous retrospective studies. [13][14][15] However, the sample size of these retrospective studies was relatively small.…”
mentioning
confidence: 99%
“…Bioactive molecules from many micro-organisms, such as the L-asparaginase enzyme, have been isolated and investigated (Savitri and Azmi 2003;Narta et al 2007). Lasparaginase is an enzyme used as a first-line treatment of patients with ALL and paediatric AML (Samudio and Konopleva 2013) and this enzyme possesses different effects depending on which micro-organism it is extracted from (Narta et al 2007;Fernandes et al 2016). Our study evaluated a new L-asparaginase enzyme extracted from Streptomyces ansochromogenes UFPEDA 3420 actinobacteria.…”
Section: Discussionmentioning
confidence: 99%